Superconductors with charge- and spin-density (Review Article): - Gabovich, A. M.; Voitenko, A. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The properties of existing superconductors with electron spectrum instabilities, namely charge-density waves (CDW`s) and spin-density waves (SDW`s), are reviewed. In such substances the supercon-ducting gap exists over the whole Fermi surface, whereas the dielectric gap emerges only on its nested sections. In particular, CDW superconductors include layered dichalcogenides, NbSe3 , compounds with the A15 and C15 structures, etc. There is a lot of evidence that high-Tc oxides also belong to this group of materials. SDW superconductors include, e.g., URu2Si 2 and related heavy-fermion compounds, Cr√Re alloys and organic superconductors. The theoretical description given in this review is based mostly on the Bilbro≈McMillan model of the partially dielectrized metal. Various thermodynamic and electrodynamic properties are calculated in the framework of this model. The main subject of the review is the nonstationary Josephson effect in tunnel junctions involving CDW or SDW superconductors. A new effect of symmetry breaking in symmetrical tunnel junctions is predicted by the authors. A comparison with experiment is given.